Report from the 24th Annual Western Canadian Gastrointestinal Cancer Consensus Conference on Colorectal Cancer, Richmond, British Columbia, 28–29, October 2022 - Sharlene Gill; Shahid Ahmed; Brady Anderson; Scott Berry; Howard Lim; Terry Phang; Ankur Sharma; Joao Paulo Solar Vasconcelos; Karamjit Gill; Mussawar Iqbal; Keith Tankel; Theresa Chan; et al. (Current Oncology, 2023)
The 24th annual Western Canadian Gastrointestinal Cancer Consensus Conference (WCGCCC) was held in Richmond, British Columbia, on 28–29 October 2022. The WCGCCC is an interactive multidisciplinary conference attended by healthcare professionals from across Western Canada (British Columbia, Alberta, Saskatchewan, and Manitoba) who are involved in the care of patients with gastrointestinal cancer. Surgical, medical, and radiation oncologists; pathologists; radiologists; and allied health care professionals such as dieticians, nurses and a genetic counsellor participated in presentation and discussion sessions for the purpose of developing the recommendations presented here. This consensus statement addresses current issues in the management of colorectal cancer.